IL-12-Induced Immune Suppressive Deficit During CD8+ T-Cell Differentiation - Renavikar, Pranav S.; Sinha, Sushmita; Brate, Ashley A.; Borcherding, Nicholas; Crawford, Michael P.; Steward-Tharp, Scott M.; Karandikar, Nitin J. (Frontiers in Immunology, 2020)
Autoimmune diseases are characterized by regulatory deficit in both the CD4+ and CD8+ T-cell compartments. We have shown that CD8+ T-cells associated with acute relapse of multiple sclerosis are significantly deficient in their immune suppressive ability. We hypothesized that distinct CD8+ cytotoxic T-cell (Tc) lineages, determined by cytokine milieu during naïve T-cell differentiation, may harbor differential ability to suppress effector CD4+ T-cells. We differentiated purified human naïve CD8+ T-cells in vitro toward Tc0 (media control), Tc1 and Tc17 lineages. Using in vitro flow cytometric suppression assays, we observed that Tc0 and Tc17 cells had similar suppressive ability. In contrast, Tc1 cells showed significant loss of suppressive ability against ex vivo CD4+ T-cells and in vitro-differentiated Th0, Th1 and Th17 cells. Of note, Tc1 cells were also suboptimal in suppressing CD4-induced acute xenogeneic graft versus host disease (xGVHD) in vivo. Tc subtypes derived under various cytokine combinations revealed that IL-12-containing conditions resulted in less suppressive cells exhibiting dysregulated cytotoxic degranulation. RNA sequencing transcriptome analyses indicated differential regulation of inflammatory genes and enrichment in GM-CSF-associated pathways. These studies provide insights into the role of T-cell differentiation in CD8 suppressive biology and may reveal therapeutically targetable pathways to reverse suppressive deficit during immune-mediated disease.